ANALISA PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENURUNAN TINGKAT KEMISKINAN DI KALIMANTAN TENGAH - Margo Tando Binti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The economic growth is used to asses the economic performance, so that the economic growth is very important because by good economic growth will open more work fields. This research aims to conduct empirical test on whether the economic growth in Central Kalimantan for the latest six years affects significantly on the decrease of Poverty Level.The research method used is descriptive method. This method is a method directing on real research issues in its practice. The obtained data are collected in research activity, then presented, described and analyzed through analysis tools applied. To answer the problem formulation and test on the hypothesis, whether there is any significant effect of the economic growth level on the decrease of Poverty level in Central Kalimantan for the latest six years, using Simple Regression Statistic Analysis.The testing results on the economic growth level for the latest six years regressed through the Poverty level in Central Kalimantan show that there is a negative correlation (- 0.356 ) but insignificant one so that the hypothesis stating that “ There is a significant effect of the economic growth level on the decrease of Poverty level in Central Kalimantan for the latest six years” is rejected.